2019
DOI: 10.1111/jcpp.13147
|View full text |Cite
|
Sign up to set email alerts
|

Annual Research Review: Umbrella synthesis of meta‐analyses on child maltreatment antecedents and interventions: differential susceptibility perspective on risk and resilience

Abstract: Child maltreatment in the family context is a prevalent and pervasive phenomenon in many modern societies. The global perpetration of child abuse and neglect stands in stark contrast to its almost universal condemnation as exemplified in the United Nation’s Convention on the Rights of the Child. Much work has been devoted to the task of prevention, yet a grand synthesis of the literature is missing. Focusing on two core elements of prevention, that is, antecedents for maltreatment and the effectiveness of (pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
92
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 166 publications
(103 citation statements)
references
References 102 publications
(121 reference statements)
4
92
1
6
Order By: Relevance
“…This study could be a small step beyond the assertion of Van IJzendoorn et al [3] that a low socio-economic level is a risk factor for the possible presence of neglect. Following the suggestions made by Schumaker [62] and Chapple and Vaske [63], it sheds some light on the controversy inasmuch that it is important to distinguish between poverty and neglect as predictors of adaptation problems.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…This study could be a small step beyond the assertion of Van IJzendoorn et al [3] that a low socio-economic level is a risk factor for the possible presence of neglect. Following the suggestions made by Schumaker [62] and Chapple and Vaske [63], it sheds some light on the controversy inasmuch that it is important to distinguish between poverty and neglect as predictors of adaptation problems.…”
Section: Discussionmentioning
confidence: 75%
“…Jonson-Reid et al [56], for example, in their systematic review of longitudinal research into experiences of child maltreatment and economic outcomes in adulthood found (despite an extremely limited evidence base) that neglect had a consistent relationship with several long-term economic outcomes such as reduced income, unemployment, lower levels of professional skills, and fewer assets. As Van IJzendoorn et al [3] recently asserted in a meta-analysis of 28 studies into neglect, socio-economic status is a predictor of elevated risk for child maltreatment.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations